Curriculum Development for Islamic Higher Education Based on Pesantren in Indonesia : Case Study Ma'had Aly Situbondo - Luluk maktumah (Academia Publication, 2024)
Ma'had Aly Salafiyah Syafi'iyah Situbondo is seen as having uniqueness and stigma differences with several traditional Islamic boarding schools in general, so that it is possible to find the concept of developing an ideal post-Islamic boarding school curriculum. This study focuses on the curriculum development model that is implemented. While the goal is to describe and analyze the curriculum development model that is implemented. The theory used as a basis is Jhon. P Miller and Wayne Seller, then strengthened by Robert S Zais and Richard A Gorton and several other theories that are relevant to the theme of the study. This study produces a new formulation of findings, namely the collaboration of the administrative model and grass roots model curriculum development with four orientations, namely; transmission, transaction, transformation and transcendence. These findings can be said to be a development as well as a correction to previous research